Land use around Corumbá IV reservoir: analysis and alignment with PACUERA guidelines - Muzzolon, Anderson; Laranja, Ruth de Paula Elias (Geografares, 2025)
Analyzing land use over time is essential for understanding the landscape’s geoecological changes, which directly affect vital resources like water and biodiversity. This study investigates changes around the Corumbá IV Reservoir to track landscape modifications and evaluate local planning since the reservoir’s establishment. We utilized digital cartographic data from IBGE (municipal boundaries), DGI/INPE (digital terrain model), MapBiomas, and satellite imagery from Google’s database, processing all inputs in QGIS 3.34 to create maps that compare observed land use with the strategy outlined in the PACUERA. Results indicate increased lakeshore urbanization between 2016 and 2023, along with reductions in forested and agropastoral areas and non-compliance with the original plan. We conclude that environmental planning needs restructuring.